HBx-Induced HSPA8 Stimulates HBV Replication and Suppresses Ferroptosis to Support Liver Cancer Progression - Wang, Yufei; Zhao, Man; Zhao, Lina; Geng, Yu; Li, Guanghao; Chen, Lin; Yu, Jingxuan; Yuan, Hongfeng; Zhang, Huihui; Yun, Haolin; Yuan, Ying; Wang, Guowen; et al. (Cancer research (Chicago, Ill.), 2023)
Hepatitis B virus (HBV) infection is a major driver of hepatocarcinogenesis. Ferroptosis is a type of iron-mediated cell death that can suppress liver transformation. Previous studies have linked HBV to ferroptosis in liver fibrosis and acute liver failure. However, whether ferroptosis is involved in HBV-mediated liver cancer is poorly understood. Here, we identified heat shock protein family A member 8 (HSPA8) as a crucial host factor that modulates HBV replication and ferroptosis in liver cancer. Hepatitis B X protein (HBx) upregulated HSPA8 by coactivating the transcription factor heat shock factor 1 (HSF1) in cells. HSPA8 enhanced HBV replication by recruiting hepatitis B core protein (HBc) to the HBV covalently closed circular DNA (cccDNA) minichromosome, forming a positive feedback loop. Moreover, HSPA8 suppressed ferroptosis in liver cancer cells by upregulating the expression of SLC7A11/GPX4 and decreasing erastin-mediated reactive oxygen species and Fe2+ accumulation in cells in vitro and in vivo. Inhibition of HSPA8 reduced the growth of HBV-positive liver tumors and increased sensitivity to erastin. In conclusion, HBx-elevated HSPA8 regulates both HBV replication and ferroptosis in liver cancer. Targeting HSPA8 could be a promising strategy for controlling HBV and hepatocarcinogenesis. HBV-induced upregulation of HSPA8 promotes hepatocarcinogenesis by suppressing ferroptosis and stimulating HBV replication, identifying HSPA8 as a potential therapeutic target in liver cancer.